Analysis of the Effect of Current Ratio and Debt To Equity Ratio on Sales at PT. Indofood Sukses Makmur Tbk in 2009-2019 - Abd Farid; Puji Muniarty (Ilomata International Journal of Management, 2021)
This research aims to identify and analyze whether there is an influence between them Curren Ratio and Debt To Equty Ratio, either partially or simultaneously to Sales at PT.Indofood Sukses Makmur Tbk. The approach taken for the use of research this is associative. The population of this study is to use financial statement data, namely data Curren Ratio consisting of current assets and current debt for Deb to Equty Ratio data consists of total debt and total equity and sales data consisting of gross sales and selling expenses for 29 years from 1990-2019 which were accessed through the website www.indofood.commethod of collection with a sample size of 11 years, namely 2009-2019. The The research sampling is purposive sampling method. While the data analysis technique using Curren Ratio, Debt To Equity Ratio, Sales, multiple linear regression, hypothesis (t test and F test), multiple correlation coefficient and multiple determination coefficient. Research result This proves that the Curren Ratio has no significant effect partially on Sales. The Debt To Equty Ratio has no significant effect partially on Sales. To be simultaneously on the Curren Ratio and Debt To Equty Ratio not effect on Sales. While the most dominant factor is the Curren Ratio and Debt To Equty Ratio to Sales is the Curren Ratio at PT.Indofood Sukses Makmur Tbk